Dramatic neurologic recovery following humeral shaft ORIF with anterior transposition and primary radial nerve repair – Case report - Sohail Qazi; Jahan Aslami; John M. Rinaldi (Journal of Orthopaedic Reports)
Background: Humeral shaft fractures are frequently complicated by radial nerve injuries, which often have poor prognosis despite surgical intervention. Early surgical repair and techniques to achieve tension-free nerve repair are critical for functional recovery. The objective of this reports is to evaluate the outcome and utility of anterior humeral transposition in primary radial nerve repair following ORIF of an open distal humeral shaft fracture. Case report: A 26-year-old male with an open distal third humeral shaft fracture and complete radial nerve transection underwent ORIF, radial nerve exploration, neural lysis, and anterior humeral transposition for primary nerve repair. The patient exhibited no radial nerve function postoperatively until the 8-month follow-up, where he showed significant improvement in motor function and sensation. By 11 months, he had near-full neurological recovery. Conclusion: Early surgical intervention and anterior humeral transposition facilitated a tension-free primary nerve repair, leading to significant functional recovery. This case underscores the importance of timely surgical management in open fractures with nerve injuries.